(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
Antibacterial and antioxidant activities of different extracts of saxicolous lichen Xanthoparmelia stenophylla sampled from Norashen, Gegharkunik Province of Armenia were studied. Methanol, ethanol and acetone extracts of lichen thalli were demonstrated to have activity against only tested gram-positive bacteria. Methanol extract of the lichen showed the highest amount of DPPH radical scavenging activity ( 68%). Our studies did not reveal any significant antibacterial and antioxidant activities of aqueous extract.